Mental workload in Mexican teachers teleworking during covid-19 pandemic - Godínez Tovar, Alejandra; Pozos-Radillo, Blanca Elizabeth; Preciado-Serrano, María de Lourdes (Acta Universitaria, 2023)
Covid-19 pandemic modified the working conditions of teachers who had to transfer their instruction to teleworking. This increased their mental workload (CMT) due to the demands of their activity and the resources to deal with this new condition. The objective of this research was to compare, according to the educational level taught, the CMT of Mexican teachers who worked in a telework modality during the covid-19 pandemic. A total of 112 teachers answered a socio-labor data questionnaire and the CMT-53 Godínez-Preciado scale. Results reported high levels of mental overload, demand for the activity, labor competence, and inadequate resolution of planned problems. In addition, in this last dimension, a significant difference was determined (F 2, 111 = 5.492, p = 0.005) between teachers in undergraduate programs compared to those teachers in secondary school.